Implementation of the Card Sort Method to Improve Student Learning Outcomes in Fiqh Learning on the Material of Halal and Haram Animals at MI Nurul Huda - Muhammad Syamsuddin; Mutatohirin (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to Implement the Card Sort Method to Improve the Learning Outcomes of Fiqh on the Material of Halal and Haram Animals for Class 6 Students of MI Nurul Huda Rangimulya Village Warureja Tegal in 2024. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were 21 students of class 6 MI Nurul Huda Rangimulya Warureja Tegal. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze the learning activities of teachers and students. The data analysis techniques used in this study are observation, tests and documentation. The results of the study indicate that the use of the Card Sort method can improve student learning outcomes in the subject of fiqh on the material of halal and haram animals. This can be seen from the learning atmosphere in class 6 becoming more lively, students becoming more active and enthusiastic in learning. This research was carried out in three stages, the first stage is the pre-cycle activity, namely finding learning outcome data before using the Card Sort method. The second stage is the implementation of Cycles I, II and III. The results of the study indicate that the use of the Card Sort Method can improve learning outcomes in the subject of Islamic jurisprudence on the material of halal and haram animals. The increase in the average percentage of learning outcomes obtained can be seen from the pre-cycle, cycle I, cycle II and cycle III. The average student learning outcomes in the pre-cycle were 33%, cycle I increased to 57%, cycle II increased to 75% and cycle III increased to 90%.